(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to analyze the degree of validity and reliability of an instrument to measure self-efficacy and metacognitive awareness of university students toward mathematics reasoning. A total of 184 respondent of a public university in Malaysia has been chosen to answer the instrument. Findings from Exploratory Factor Analysis (EFA) support three dimensions of self-efficacy and six dimensions of metacognitive awareness of students toward mathematics reasoning that has been conceptualized. The overall internal consistency reliability of Cronbach Alpha coefficients was above 0.9. Based on the analysis performed, it can be concluded that developed instrument has sufficient evidence of validity and reliability to measure self-efficacy and metacognitive awareness of university students toward mathematics reasoning.